Lean Approach for Waste Reduction in Production Line by Integrating DMAIC, VSM, and VALSAT Method (Study Case: Assembling Bracket Manufacturing Automotive Industry) - Muhammad Kholil; Adizty Suparno; Sulaiman Bin Haji Hasan; Rizki Aprilia (Institute of Computer Science (IOCS), 2022)
The automotive manufacturing industry is a manufacture that produces four-wheeled automotive accessories parts. One of the products is the audio unit and bracket. This research aims to reduce waste in production and reduce cycle time, affecting increasing production output to adapt it to customer needs. Waste identification by integrating lean six sigma, namely DMAIC, VSM, and VALSAT. Based on the analysis results, it was found that the four biggest wastes were motion, inventory, waiting, and process. After carrying out the repair activities, the cycle time decreased at station three from 704 seconds to 246 seconds, thereby increasing the capacity efficiency from 75% to 91 %.